American women testifyng to the european conquest in Seed of the Gods,legendary Peru (2000) by Lucía Fox & Island Beneath the Sea (2009) by Isabel Allende - Rojas Benavente, Lady (2015)
On the basis of the evidence that several Latin American writers are inspired from historical facts like the European colonization of the American continent that are vital in the sociohistorical evolution of peoples, I am interested in exploring in this research how female characters are depicted. My hypothesis is that there is in contemporary novelists — Peruavian-American Lucía Fox and Chilean- American Isabel Allende— a clear and feminist awareness of the interrelationship between fiction and the historical and historiographic record in the literary history of Latin America My goal is to put the record straight about the official stories where women’s involvement has been purged clean f their pages; and in so doing women will be able to shape new and dynamic representations of women in colonial times of various peoples and countries of the Central American, Caribbean and South American regions. My interest focuses on a critical analysis of two characters created in novels that bear witness to and rise up against the coercive systems imposed by Spanish and French colonialism by means of women’s domesticity and Africans’ slavery.